(untitled) (Research, Society and Development, 2022)
The spontaneous plants, also known as weeds or invasive plants, are plants belonging to several taxonomic groups, which have in common the ability to grow in different environments without being cultivated. In pasture areas, infestation by spontaneous plants, in addition to reducing productivity, can also interfere with the health of animals, as they present structures such as thorns and branches capable of causing physical damage, and even containing substances capable of causing intoxication. Considering that the Amazon region has a diverse and little studied flora, this work aimed to carry out a survey and mapping of spontaneous plant species occurring in three pasture areas (named areas 1, 2 and 3) located in Belém’s Campus from the Universidade Federal Rural da Amazônia (UFRA), considering that their precise identification is essential for their proper management. Through this study, 20 species were identified, distributed in 10 families; being the family Cyperaceae Juss. the most predominant, with 52.33% of the individuals collected; the species Cyperus brevifolius (Rottb.) Endl. ex Hassk. and Ipomoea asarifolia (Desr.) Roem. & Schult. showed the highest values of IVI in the 3 areas worked, and pasture 1 showed the highest degree of infestation by spontaneous species (Nti=349 specimens) among the 3 areas. The data obtained are relevant for evaluating the current state of the pastures, as well as providing data that can help in the management of spontaneous plants present in the areas.